Evaluation of Fire Resistance, Thermal and Optical Properties of Bleached Kraft Paper Using some Boron Compounds and Soy Protein Binders - Evren Ersoy Kalyoncu; Derya Ustaömer (BioResources, 2025)
Bleached kraft papers obtained from unbeaten (UB) and beaten (B) pulps were separately treated with zinc borate (ZB) and boric acid (BA) to improve their flame retardancy. The immersion method was chosen for application, and natural soy protein was added as a binder. The combined effect of soy protein (SP) and used boron compounds was observed. To investigate the thermal and fire resistance properties of the bleached kraft papers (BKP), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), limited oxygen index levels (LOI), and UL-94 burning test were performed.  The brightness and color parameters (L*, a*, b*, ∆L*, ∆a*, ∆b*, ∆E*) were also measured to determine the optical properties. The results showed that the combined effect of ZB and BA used with SP increased the flame resistance of kraft papers. The bleached kraft paper treated with BA had better flame retardancy in terms of LOI and UL-94 burning tests than paper treated with ZB. These results were also consistent with the TGA and DSC findings. Furthermore, the optical properties varied slightly depending on the chemical usage rates. Zinc borate and SP had a more positive effect on the brightness values of the bleached kraft papers compared to BA and SP.